2021
DOI: 10.1111/ecpo.12197
|View full text |Cite
|
Sign up to set email alerts
|

The economic impact of political instability and mass civil protest

Abstract: An extensive literature has examined the economic effects of non‐violent political instability events. Nonetheless, the issue of whether economies react differently over time to such events remains largely unexplored. Using synthetic control methodology, which constructs a counterfactual in the absence of political instability, we estimate the output effect of 38 regime crises in the period 1970–2011. A crucial factor is whether crises are accompanied by mass civil protest. In the crises accompanied by mass ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…This impairs trade and economic activity exacerbating the adverse economic effects (Veninga and Ihle, 2018). Moreover, economic agents may interpret such unrest as signaling an impeding major political change and accordingly adjust their economic decisions (Matta et al. , 2021).…”
Section: Methodology and Empirical Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…This impairs trade and economic activity exacerbating the adverse economic effects (Veninga and Ihle, 2018). Moreover, economic agents may interpret such unrest as signaling an impeding major political change and accordingly adjust their economic decisions (Matta et al. , 2021).…”
Section: Methodology and Empirical Findingsmentioning
confidence: 99%
“…Invariably it spills-over to the economy through various channels including, capital markets and investment decisions that can be dissuaded in view of the uncertainty the social turbulence and upheaval tends to generate (inter alia: Abu Murad and Alshyab, 2019;Aisen and Veiga, 2013;Dorsett, 2013). Matta et al (2021) argue that mass protests and social unrest could be construed by economic agents as signaling the possibility of a major or indeed fundamental political and economic regime change and this possibility exacerbates the negative impact exerted on the economy and economic activity. Veninga and Ihle (2018) note that political instabilities do not only cause uncertainty that affects economic agents such as consumers and traders but can also render institutions dysfunctional.…”
Section: Introductionmentioning
confidence: 99%
“…Matta et al (2022) find that regime crises accompanied by mass civil protest are especially likely to result in a lengthy fall in output.…”
mentioning
confidence: 89%
“…Outside the political risk arena but still connected with political issues on financial crisis and recessions, Compaor e et al (2020) highlighted the contributions of conflicts and political instability on the probability of banking crisis, confirming that these events are associated with a higher probability of a systemic banking crisis. Matta et al (2017) studied political instability vested as regime crisis and mass civil protests events to fall in country GDP. They concluded that regime crisis with mass civil protests causes an immediate drop in economic output which does not restore in the following years.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2020) highlighted the contributions of conflicts and political instability on the probability of banking crisis, confirming that these events are associated with a higher probability of a systemic banking crisis. Matta et al. (2017) studied political instability vested as regime crisis and mass civil protests events to fall in country GDP.…”
Section: Literature Reviewmentioning
confidence: 99%